Life expectancy of cats in Britain: moggies and mollies live longer - Fernando Mata (PeerJ)
The domestic cat (Felis catus) has been a popular companion animal for about 12,000 years, initially valued for rodent control before evolving into pets that provide affection and companionship. Unlike dogs, cats were not selectively bred for specific roles until the late 1800s, resulting in breeds defined primarily by appearance, which sometimes leads to genetic disorders. Modern animal welfare concerns emphasize longevity and health, prompting research into factors affecting cat lifespans, including sex, reproductive status, and breed. This study aims to expand on previous UK research by analyzing these interactions and highlighting the potential negative impacts of pure breeding on cat health. Data from 7,708 cats receiving veterinary care in the UK during 2019 were analyzed, focusing on reproductive status, breeding status, age at death, and sex. Data were analyzed using ANOVA and Cox proportional hazards models to assess survival differences. The overall mean lifespan of cats in the UK is 11.83 years. Analysis indicates that male cats live shorter lives than females, attributed to higher trauma rates and health issues among males. Neutered/spayed cats generally exhibit longer lifespans compared to entire cats. Tom cats have the shortest lifespan, while spayed females (mollies) live the longest. Moggies tend to outlive both pure and cross-bred cats, suggesting that genetic diversity may contribute to greater longevity. The results of this study emphasize the influence of sex, reproductive status, and cat type on feline lifespan, highlighting the need for targeted health interventions, particularly for male cats. The findings underscore the complex interplay of genetic and environmental factors in determining the health and longevity of domestic cats. This research not only contributes to existing knowledge but also advocates for the consideration of these variables in future studies and veterinary practices.